Teacher candidates as student partners in decoding the disciplines research: Decoding how university students contextualize historical documents - DiCostanzo, Ryan; Discenza, Anthony; Langone, Jenna; McBrady, Jared (International Journal for Students as Partners, 2024)
This study examines the role of secondary teacher candidates as student partners in research into undergraduate students’ historical cognition while contextualizing documents. It highlights the unique role of teacher candidates as near-peer interviewers and change agents within higher education and secondary curricula. Through using decoding the disciplines methodology to solicit student voice in near-peer interviews, teacher candidates identified areas for curricular change in teaching contextualization in university history courses. The involvement of teacher candidates extended beyond the university classroom and informed their future work in secondary education. Decoding experiences in university courses provided teacher candidates with insights into supporting secondary pupils’ abilities to contextualize historical sources. This research demonstrates the potential of teacher candidates as near-peer interviewers and curricular change agents in secondary and higher education. Collaborative partnerships between teacher candidates and faculty can lead to meaningful curricular changes and effective teaching practices in higher education and secondary education contexts.